The Actual Incidence and Types of Hearing Losses in Bullous Myringitis: Case Series and Systematic Review. Issue 7 (August 2021) - Ungar, Omer J.; Handzel, Ophir; Oron, Yahav; Eta, Rani Abu; Muhanna, Nidal; Warshavsky, Anton; Horowitz, Gilad; Simani, Liam
Abstract : Objective: To calculate the incidence of sensorineural hearing loss (SNHL; pure or as part of a mixed hearing loss, MHL) among bullous myringitis (BM) patients with a coexisting HL to assess whether steroidal treatment should be initiated even before the findings of a formal audiogram are available. Methods: Retrospective medical record review in a tertiary referral center and systematic review of the English literature. Results: The medical records of 81 patients with BM were retrieved among whom 50 patients (62%) had actually sustained a HL, although only 39/81 patients reported a HL when asked. Twenty-four patients had a MHL, 18 had a SNHL, and eight had a conductive HL (CHL). The systematic review included 106 ears: 17 had no HL, 53 had a MHL, 20 had a SNHL, and 16 had a CHL. The combined published and current results yielded a SNHL and MHL rates of 38/139 (27%) and 77/139 (55%), respectively of all BM patients with confirmed HL. Conclusion: BM is intuitively associated with a CHL resulting from the impeded function of the affected middle ear. Medical history and physical examination are not sufficient to exclude a SNHL in BM patients, and formal audiometry is mandatory for exclusion/confirmation in this setting. Nevertheless, steroidal treatment should not be delayed until the performance of formal audiometry because the actual rate of pure CHL in this setting is very low. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text